2006
DOI: 10.1111/j.1476-4431.2006.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the percentage of prescribed enteral nutrition actually delivered to hospitalized companion animals

Abstract: Objective: To investigate the percentage of prescribed enteral nutrition that is actually delivered; the percentage of goal feeds [defined in terms of the animal's estimated resting energy requirement (RER)] that are delivered; and the reasons animals are under or overfed in a small animal teaching hospital. Design: Prospective investigation. Setting: Matthew J. Ryan Veterinary Hospital of the University of Pennsylvania. Animals: All dogs and cats that received tube feeding while admitted to the Ryan Veterinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Veterinary patients with critical illness are often partially or completely anorexic and in need of nutritional support. The importance of nutritional support in critically ill small animal patients is widely accepted 1–5 . Although some debate still exists, the advantages of enteral nutritional (EN) support when compared with methods of parenteral nutritional (PN) support are well documented in critically ill people 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary patients with critical illness are often partially or completely anorexic and in need of nutritional support. The importance of nutritional support in critically ill small animal patients is widely accepted 1–5 . Although some debate still exists, the advantages of enteral nutritional (EN) support when compared with methods of parenteral nutritional (PN) support are well documented in critically ill people 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human and veterinary patients have shown a discrepancy between the amount of nutrition prescribed by the clinician, and the amount actually delivered to the patient 1,2,6,8 . Identification of causes for this discrepancy has been the focus of multiple studies 1,2,4,6,8–12 . In both veterinary and human studies, cessation of feeding during diagnostic or therapeutic procedures was a common barrier to nutrient delivery 1,2,6,8,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that estimated RER was met in only 5% of dogs was likely due to slow ramping rate of the constant rate infusion and relatively short period of intrajejunal feeding in the ICU. In contrast, a previous veterinary study of nasoesophageal, esophagostomy, and gastrostomy tubes that set a goal of feeding at 100% RER on the second day of feeding reported that animals received a median of 90% of goal feeds by intermittent bolus feeding via the tube. A faster ramping rate might have increased the number of dogs receiving 100% of estimated RER by the time of discharge.…”
Section: Discussionmentioning
confidence: 73%